Direct Conversion of Benzothiadiazole to Benzimidazole: New Benzimidazole‐Derived Metal–Organic Frameworks with Adjustable Honeycomb‐Like Cavities. Issue 20 (12th March 2019) - Zhao, Yingnan; Han, Xiao; Yu, Feihu; Wei, Donghui; Cheng, Qing; Meng, Xiangru; Ding, Jie; Hou, Hongwei
Abstract: Up to now, the direct conversion of the thiadiazole ring to other heterocyclic rings has been a very challenging task. Herein, a Cd II ‐mediated alcohol‐substitution strategy for direct conversion from benzothiadiazole to benzimidazole is reported. Experimental and molecular modeling studies on the role of the chelated metal ion in this in situ alcohol‐substitution reaction revealed that it serves as an all‐rounder that is involved in the insertion of alcohol, activation of the thiadiazole ring by coordinative interaction, and the sulfur‐extrusion process. Interestingly, the insertion of alcohol occurs much earlier than the sulfur‐extrusion process, supported by a water‐mediated proton‐transfer process. This strategy also is suitable for constructing new benzimidazole‐derived MOFs [Cd2 (HMBIDC 2− )2 ]⋅ 4 H2 O (Cd‐BID‐MOF‐1, HMBIDC 2− =2‐methyl‐1 H ‐benzimidazole‐4, 7‐dicarboxylate) and [Cd2 (HPBIDC 2− )2 ]⋅ 1/3 H2 O (Cd‐BID‐MOF‐2, HPBIDC 2− =2‐(3‐hydroxypropyl)‐2 H ‐benzimidazole‐4, 7‐dicarboxylate). Because the terminal hydroxyl group on the imidazole ring protrudes into the circular channel in rhombohedralCd‐BID‐MOF‐2, the cavity is closer to hydrophilic than the honeycomb‐like cavity inCd‐BID‐MOF‐1 with similar 3D structure. This rare observation will provide a new strategy to develop in situ ligand‐reaction synthesis of functional MOFs and useful chelation‐assisted catalytic reactions in heteroaromatic chemistry. Abstract : Ring the changes : A cadmium(II)‐mediated alcohol‐substitution strategy for direct conversion of a thiadiazole ring to an imidazole ring, as well as the construction of benzimidazole‐derived metal–organic frameworks showing adjustable cavities is reported (see figure).